2018
DOI: 10.1016/j.jbankfin.2017.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Option-implied objective measures of market risk

Abstract: Foster and Hart (2009) introduce an objective measure of the riskiness of an asset that implies a bound on how much of one's wealth is 'safe' to invest in the asset while (a.s.) guaranteeing no-bankruptcy in the long run. In this study, we translate the Foster-Hart measure from static and abstract gambles to dynamic and applied finance using nonparametric estimation of risk-neutral densities from S&P 500 call and put option prices covering 2003 to 2013. This exercise results in an option-implied market view of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Our empirical results extend those of Rompolis (2010), and Rompolis and Tzavalis (2010) from the equity market to the interest rate markets. Similarly, we contribute to the literature on risk-neutral density properties, by partially extending the results from equity markets (Bali and Murray, 2013;Leiss and Nax, 2018;Barletta et al, 2019) to the interest rate markets. This paper is organized as follows: Section 2 briefly introduces the canonical valuation notation as in Stutzer (1996).…”
Section: Introductionmentioning
confidence: 91%
“…Our empirical results extend those of Rompolis (2010), and Rompolis and Tzavalis (2010) from the equity market to the interest rate markets. Similarly, we contribute to the literature on risk-neutral density properties, by partially extending the results from equity markets (Bali and Murray, 2013;Leiss and Nax, 2018;Barletta et al, 2019) to the interest rate markets. This paper is organized as follows: Section 2 briefly introduces the canonical valuation notation as in Stutzer (1996).…”
Section: Introductionmentioning
confidence: 91%
“…Based on the research carried out in Polish and foreign literature, it was found that there is a need to support the financial risk management process of supply chain projects, using the Foster-Hart measure, moreover, it is a littleconsidered subject. Literature is focused on this measure in the context of the use for investment in shares [Leiss, Nax 2018], and not for other projects that may or even are always associated with income's generation. The problem that is associated with the use of this measure concerns the adaptation of its form to the mentioned process.…”
Section: Foster-hart Measure and Supply Chain Projectsmentioning
confidence: 99%
“…Interestingly, even if one 3 Aumann & Serrano's (2008) and Foster & Hart's (2009) indices of risk have been extended to gambles with an infinite support (Homm & Pigorsch, 2012;Schulze, 2014;Riedel & Hellmann, 2015) and to gambles with uncertainty, i.e., unknown probabilities (Michaeli, 2014). These indices have also been applied to study real-life investment strategies (Kadan & Liu, 2014;Bali et al, 2015;Anand et al, 2016;Leiss & Nax, 2018). gamble second-order stochastically dominates another gamble, it is not sufficient for a uniform ranking among all risk-averse agents in every decision problem (see, e.g., the analysis of capital allocation decisions in Landsberger & Meilijson, 1993).…”
Section: Related Literature and Contributionmentioning
confidence: 99%